Adventure education as aesthetic experience. Issue 4 (2nd October 2018) - Ingman, Benjamin C.
ABSTRACT: This study is an investigation of what happens to participants during their adventure education (AE) experiences and the meanings they ascribe to those experiences. These topics were explored through the qualitative framework of educational connoisseurship and criticism at three sites: a backpacking expedition, a challenge course and a multi-activity adventure programme. Through 183 hours of observation and 74 interviews with 41 participants, the qualities of AE as aesthetic experience were revealed. This conception of AE experience is characterised through sensory encounters, full attention and aesthetic paradox. Findings are supported with the voices of participants, and the significance of this conception of AE experience is discussed.